Creating a learning space: Using experiential learning and creativity in the teaching and learning of social pedagogy. Issue 1 (15th July 2020) - Charfe, Lowis; Gardner, Ali; Greenhalgh, Edwin; Marsden, Helen; Nester, Daniel; Simpson, Lindy
Abstract : This reflective account has been co-developed, produced and written by students and the teaching staff on the BA Hons Social Pedagogy, Advocacy, and Participation degree at the University of Central Lancashire. The account focuses on the use of experiential and creative teaching methods utilised on the course and how this enhances the understanding and application of social pedagogy. The article critically analyses the link between how the social pedagogical theories, concepts and methods are taught and the advancement of the student and lecturer understanding of this field of study. In developing this reflective account, the current student cohort and lecturers were given the opportunity to participate in a collaborative reflection across all years of the course. They discussed their own learning journey and how this has shaped development of creativity within their practice. During the discussions around the use of blended, experiential learning and creativity, three key themes emerged: (1) the importance of the environment on creativity and learning; (2) the importance of relationships, creativity and learning; and (3) Haltung, psychological safety and creativity. In the reflections on what they have learned so far, the students and lecturers hope to inspire other education providers to use creative and experiential teaching methods within their courses. The authors feel that the reflective account contains useful information around the learning that has taken place over the last three years of this course being taught.